IMPROVEMENT OF SHORT STORY WRITING SKILLS USING COMMUNICATIVE METHODS IN CLASS X STUDENTS OF SMAN 16 MAKASSAR - Mardiana; Muliadi; Kasman F Amin (Citra Dharma Cindekia, 2022)
The purpose of this study was to describe the learning process and improve short story writing skills using the communicative method of class X SMAN 16 Makassar students. The research subject is class X with 36 students, the type of research used is classroom action research, the data collection method in the research uses test techniques, observation sheets and documentation, data analysis techniques used in the research are qualitative and quantitative techniques, the results of the research show that using the communicative method can improve students' short story writing skills. The process of improving learning to write short short stories by means of students learning short story material, intrinsic elements, and steps to write short stories. Before being given the action, a pretest was held to determine the students' initial skills in writing short stories in the pre-cycle. The results show that in class X the average score generated is 60.41. Then, the communicative method was carried out in cycle 1, so that the results increased by 69.30. After the second cycle of action was carried out, the results again increased by 80.58. Based on the results of the research and discussion, it can be concluded that there was an increase in the short story writing skills of students of class X IPA 6 when using the communicative method.